Pengaruh Kerjasama Tim dan Komunikasi terhadap Kinerja Pegawai Biro Organisasi dan Sumber Daya Manusia Kementerian Perindustrian Republik Indonesia - Tiara Azkia Zarlianty; Syahrial Addin; Yulia Mujiaty (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This study aims to determine the effect of teamwork and communication on employee performance at the Bureau of Organization and Human Resources of the Ministry of Industry of the Republic of Indonesia. Employee performance is an important aspect in achieving organizational goals, which is influenced by the effectiveness of cooperation between team members and communication established in the work environment. The method used in this study is a quantitative approach with a total sampling technique, where the entire population of 40 people was sampled. Data were collected through questionnaires and analyzed using SPSS version 25 with validity tests, reliability, classical assumption tests, multiple linear regression, t-tests, f-tests, and coefficient of determination tests. The results showed that teamwork has a significant positive effect on employee performance with a t-value of 2.222 and a significance of 0.032. And communication also has a positive effect on employee performance with a t-value of 4.239 and a significance of 0.000. The coefficient of determination of 48% indicates that teamwork and communication contribute to improving employee performance, while the rest is influenced by other factors outside this research model. This study concluded that increasing teamwork and effective communication can significantly improve employee performance.